Treatment of gonadotropin deficiency during the first year of life: long-term observation and outcome in five boys. Issue 5 (25th April 2019) - Kohva, Ella; Huopio, Hanna; Hietamäki, Johanna; Hero, Matti; Miettinen, Päivi J; Raivio, Taneli
Abstract: STUDY QUESTION: What is the peripubertal outcome of recombinant human FSH (r-hFSH) treatment during minipuberty in boys with congenital hypogonadotropic hypogonadism (CHH)? SUMMARY ANSWER: Sertoli-cell response to r-hFSH, given during the minipuberty of infancy, appears insufficient to maintain Sertoli cell function throughout childhood, as evaluated by inhibin B measurements. WHAT IS KNOWN ALREADY: Severe CHH in boys can be diagnosed during the minipuberty of infancy. Combined gonadotropin treatment at that age is suggested to improve testicular endocrine function and future fertility, yet long-term evidence is lacking. STUDY DESIGN, SIZE, DURATION: In this retrospective cohort study, we describe five CHH boys treated with r-hFSH in Helsinki University Hospital or Kuopio University Hospital between 2004 and 2018. Immediate follow-up data (0.1–1.4 months after cessation of the gonadotropin therapy) was available for four boys and long-term observations (at the age of 10.0–12.8 years) was available for three boys. As a retrospective control cohort, we provide inhibin B values of eight untreated CHH boys at the age of 12.7–17.8 years. PARTICIPANTS/MATERIALS, SETTING, METHODS: Four patients had combined pituitary hormone deficiency, and one had CHARGE syndrome due to a CHD7 mutation. The patients were treated at the age of 0.7–4.2 months with r-hFSH (3.4 IU/kg–7.5 IU/kg per week in 2 or 3 s.c. doses for 3–4.5 months) combined with T (25 mg i.m. monthly for three months for the treatment of micropenis). Inhibin B was chosen as the primary outcome measure. MAIN RESULTS AND THE ROLE OF CHANCE: During the r-hFSH + T treatment, inhibin B increased from 76 ± 18 ng/l to 176 ± 80 ng/l ( P = 0.04) and penile length increased by 81 ± 50% ( P = 0.04). Unexpectedly, two boys with robust inhibin B responses in infancy demonstrated low inhibin B values in peripuberty: declining from 290 ng/l (4 months) to 16 ng/l (12.4 years), and from 207 ng/l (6 months) to 21 ng/l (12.8 years). All boys underwent orchiopexy at 2.0 ± 0.7 years of age. Inhibin B values in long-term follow-up, available for the three boys, did not significantly differ from the untreated CHH controls. LIMITATIONS, REASONS FOR CAUTION: Limitations of this retrospective study are the small number and heterogeneity of the patients and their treatment schemes. WIDER IMPLICATIONS OF THE FINDINGS: We describe the first long-term follow-up data on CHH boys treated with r-hFSH and T as infants. The results from this small patient series suggest that the effects of infant r-hFSH treatment may be transient, and further longitudinal studies are required to determine the efficacy of this treatment approach to optimise the fertility potential in this patient population. STUDY FUNDING/COMPETING INTEREST(S): This work was supported by the Finnish foundation for Pediatric Research, the Academy of Finland and the Emil Aaltonen Foundation. The authors have no competing interests. TRIAL REGISTRATION NUMBER: Non-applicable.